Emergency management: microbial keratitis - Arunga, Simon; Burton, Matthew (Community eye health, 2018)
Microbial keratitis is an infection of the cornea that can be caused by bacteria, fungi or protozoa such as Acanthamoeba spp. In low- and middle-income countries, management is often more challenging because of late presentation, the use of traditional eye medicines, insufficient diagnostic support, a lack of effective drugs and insufficient keratoplasty services. Our experience in East Africa is that most patients will visit a primary health centre within a day or two of onset of symptoms, but may take another two weeks to reach the eye unit; by which time it can be too late to save the eye. All health care workers, including front-line primary health workers, must therefore know how to identify microbial keratitis early, provide immediate treatment, refer patients for specialist treatment and make sure they are able to take up the referral.
Keywords: Emergency management; Microbial keratitis